Should cross-border banking benefit from the financial safety net? - Bertay, Ata Can; Demirgüç-Kunt, Asli; Huizinga, Harry (Journal of Financial Intermediation, 2016)
Using bank-level data from 84 countries, we find that a higher degree of bank internationalization is associated with higher interest expenses. Internationalization is proxied by a bank's share of foreign liabilities in total liabilities or a Herfindahl index of international liability concentration. Bank interest expenses rise relatively more with internationalization if the bank is underperforming or headquartered in a country with weak public finances, and especially at times of weak world output growth. These results suggest that liability holders of distressed internationalized banks expect less from the financial safety net since lack of an efficient recovery and resolution regime for international banks can make their insolvency very costly to deal with.